Sustainable entrepreneurship and corporate social responsibility: Analysing the state of research - Rosário, Albérico Travassos; Figueiredo, José (Sustainable environment, 2024)
At a basic level, entrepreneurship refers to an individual or a small group of partners that intend to create a new business. Entrepreneurship is at the forefront of any competitive economy due to the creation of new products and services. In other words, entrepreneurship is associated with economic wealth, growth, and innovation. The usage of resources in the creation of new businesses needs to be rational because investors normally are risk averse, and the usage of resources must take into account the possible damage to the planet. In other words, entrepreneurs and the sustainability of the planet are interconnected. Beyond this, entrepreneurs need to take care of the corporate social responsibility of each new business, considering the interests of all stakeholders. Nevertheless, existing research has not shown in full all the research streams, how they interact with each other and their potential knowledge development. The methodological approach is based on a literature review using Scopus® databases under the PRISMA (Preferred Reporting Items for Systematic review and Meta-Analysis). This paper aims to identify research trends in the field through a Systematic Bibliometric Literature Review of social entrepreneurship and corporate social responsibility research, with a literature review based on SCOPUS, the world’s most important peer-reviewed database in the academic world, and using the PRISMA protocol, which contributes to an increased knowledge on the subject. The review includes 69 articles published in the Scopus® database, presenting up-to-date knowledge on the topic.